Analysis of Logistics Management Strategy in Increasing Drug Availability at Dalu Sepuluh Tanjung Morawa Community Health Center - Rahayu, Sri; Syaharani, Latifah; Indah Karera, Anggi; Rabitha Khailila Ihrom Nasution (Jurnal Kesmas Prima Indonesia, 2025)
Drug logistics management is a crucial aspect in ensuring drug availability in primary healthcare facilities. This study aims to analyze logistics management strategies to improve drug availability at the Dalu Sepuluh Tanjung Morawa Community Health Center. The research method used was descriptive qualitative, with data collection techniques through in-depth interviews with two key informants and direct observation. The results showed that all stages of logistics management—planning, procurement, storage, distribution, and disposal—have been implemented in accordance with applicable standard operating procedures (SOPs) and regulations. Planning was carried out using LPLPO and referring to DOEN. Drug storage applies the FIFO and FEFO principles, but storage space is still limited. Distribution is carried out routinely every two months, although delays are often encountered by the district pharmacy installation. Stock monitoring is still predominantly manual, despite the availability of applications such as SIMPUS and SIODANG. The process of eliminating expired drugs has not been routinely scheduled due to limited funds and space. In conclusion, the logistics strategy has been implemented comprehensively, but improvements are still needed in technology integration, storage capacity, human resource training, and drug disposal management to ensure optimal and sustainable availability.